Phytotoxicity of Natural Molecules Derived from Cereal Crops as a Means to Increase Yield Productivity - Hiwa M. Ahmed; Ehsan Amiri-Ardekani; Sayed Ebadi (International Journal of Agronomy)
Phytotoxicity including autotoxicity and allelopathy is the immediate or indirect biochemical impact of one organism on the germination, growth, survival, and reproduction of other organisms or improvement of neighbouring plant species through the arrival of substances into the environment. This biological phenomenon effect might be either growth-enhancing (synergistic) or inhibiting (hostile), contingent upon the chemical substances delivered from donor plants and target species. Allelopathy has been viewed not just as a nature-accommodating way to control unwanted plant spices and biocidal products, but, additionally, a potential explanation for causing autotoxicity in yield. The application of chemical agents to reduce weed infestation may have negative consequences on human health as well as the environment. Plants with allelopathy activities derived from secondary metabolites could be an alternative strategy and have an expected function in sustainable weed biocontrol and boost global agricultural production and food security. Thus, protecting biodiversity, ensuring food safety, improving food, and nutrient quality, as well as crop production, are urgently needed as population and consumption are increasing. So, the objective of this study is to present recent advancements on phytotoxicity and allelopathic effect of plant extracts (sorghum, sunflower, rice, and corn), for sustainable food and crop production in agroecosystems.